Effect of Rooibos and Honeybush Tea Extracts Against Botrytis cinerea - Coetzee, G.; Marx, I.J.; Pengilly, M.; Bushula, V.S.; Joubert, E.; Bloom, M. (South African Journal of Enology and Viticulture, 2016)
Green tea extracts from the indigenous South African rooibos (Aspalathus linearis) and honeybush (Cyclopia species) plants were evaluated as potential antifungal agents against the plant pathogen Botrytis cinerea. When applied at 10 mg/ml, the tea extracts stimulated biomass production in B. cinerea by more than 3-fold after 24 hrs. This induction could not be linked directly to the presence of selected micro- and macronutrients or antioxidants in the extracts, suggesting a complex set of yet unidentified factors that may act synergistically to enhance cell growth. However, when applied at 100 mg/ml, the A. linearis and C. genistoides extracts reduced spore germination of B. cinerea by 33.3% and 16.7%, respectively. This suggests that the tea extracts contain active compounds that should be further investigated for their potential as natural anti-fungal agents.